(untitled) (Mugda Medical College Journal, 2026)
Percutaneous nephrolithotomy (PCNL) is the standard treatment for large or complex renal stones. Supracostal puncture offers an alternative access route when infra-costal access is challenging, but it carries potential risks. A cross-sectional, observational study was conducted in the Department of Urology, Mugda Medical College Hospital, Dhaka, Bangladesh, between January 2022 and December 2024, to evaluate the safety, success, and stone-free rates of supracostal PCNL and identify factors predicting outcomes in patients with renal stones. A total of of 70 patients (40 males and 30 females) undergoing PCNL via supracostal puncture were included in this study. Stone characteristics, puncture levels, operative details, complications, and stone-free rates were analyzed. The mean age of the patients was 29.6±8.4 years. Stone-free rate (SFR) was 89.4%. Complications occurred in 14.3% of the patients including intraoperative haemorrhage (5.7%), hydrothorax (4.3 pneumothorax (2.9%), and delayed haemorrhage (1.4%). Multivariate logistic regression analysis showed that stone size (OR=0.65, 95% CI 0.48–0.89, p<0.01), stone type (staghorn vs non-staghorn; OR=0.42, 95% CI 0.18–0.98, p<0.05), and degree of hydronephrosis (OR=1.34, 95% CI 1.01–1.78, p<0.05) are independent predictors of stone-free status. However, gender, puncture level, and number of tracts were not significant predictors (p>0.05) Supracostal PCNL is a safe and effective approach for complex renal stones when infra-costal access is not feasible. Careful patient selection and surgical expertise are critical to maximizing stone-free rates and minimizing complications. Mugda Med Coll J. 2026; 9(1): 48-52